Smoking associates with distinct clinical phenotypes in patients with systemic lupus erythematosus: a nationwide Danish cross-sectional study - Søren Jacobsen; Asta Linauskas; Salome Kristensen; Niels Steen Krogh; Lene Dreyer; Anne Troldborg; Anne Voss; Henrik Christian Bidstrup Leffers; Jesper Lindhardsen; Prabhat Kumar; Lars Juul; Bent Deleuran (Lupus Science and Medicine)
Objectives SLE displays large clinical heterogeneity that beyond genetic factors may be determined by environmental exposures. In this Danish nationwide study, we aimed to determine if clinical subsets of SLE were associated with smoking history.Methods At each of six participating centres, incident or prevalent inpatients and outpatients with SLE were consecutively included. Manifestations forming the basis of SLE classification were registered in an electronic chart system. Patients also provided questionnaire-based data on environmental exposures, including smoking history. Hierarchical cluster analysis was conducted to determine and characterise subsets of patients with similar traits of disease manifestations. Levels of smoking exposure by pack-years were correlated to the identified SLE subsets, as well as discrete SLE manifestations.Results The cohort consisted of 485 patients (88% women and 92% Caucasian) with SLE of which 51% were ever smokers. Common disease manifestations comprised non-erosive arthritis (81%), malar rash (57%), lymphopenia (55%), photosensitivity (50%) and persistent proteinuria (41%). We identified three distinct phenotypic clusters characterised by their preponderance of (A) neurological, serosal and mucosal involvement; (B) renal, haematological and immunological disorders; and (C) acute and chronic skin manifestations. Cluster B was the youngest and had the lowest level of smoking exposure. Age-adjusted regression analyses showed that compared with never smokers a smoking history of >20 pack-years was associated with neurological disorder (OR=3.16), discoid rash (OR=2.22), photosensitivity (OR=2.19) and inversely with haematological disorder (OR=0.40), renal disorder (OR=0.40) and non-erosive arthritis (OR=0.45), p<0.05 for all.Conclusions Our findings support that SLE presents in varying clinical phenotypes and suggest that they may have differentiated associations with smoking history.